Overview Results of Optic Neuritis After Steroid Therapy - Ricky O Sembiring; Bambang Setiohadji; Ine Renata Musa; Feti Karfiati (Majalah Oftalmologi Indonesia, 2015)
Background: Optic neuritis is an inflammatory condition of the optic nerve characterized by a sudden onset of unilateral visual loss, usually affecting young females. Recent studies have shown that treatment with intravenous methylprednisolone results in more rapid recovery of vision. The aim is to describe early visual outcome after methylprednisolone treatment according to Optic Neuritis Treatment Trial (ONTT) in optic neuritis. The outcome will be visual acuity and color vision. Method: This is a retrospective observational study. The data were collected from medical records of patients diagnosed as optic neuritis who had steroid treatment, from January 2009 to December 2012. Result: There were increased visual acuity in 92.4% eyes within 7-11 days after administration of parenteral methylprednison, as well as color vision in 83.0% eyes. Conclusion: Methylprednisolone treatment will improve visual acuity and color vision in early follow up. Keywords: Optic neuritis, visual acuity, color vision